Evaluation of a sensor algorithm for motor state rating in Parkinson's disease. (July 2019) - Johansson, Dongni; Thomas, Ilias; Ericsson, Anders; Johansson, Anders; Medvedev, Alexander; Memedi, Mevludin; Nyholm, Dag; Ohlsson, Fredrik; Senek, Marina; Spira, Jack; Westin, Jerker; Bergquist, Filip
Abstract: Introduction: A treatment response objective index (TRIS) was previously developed based on sensor data from pronation-supination tests. This study aimed to examine the performance of TRIS for medication effects in a new population sample with Parkinson's disease (PD) and its usefulness for constructing individual dose-response models. Methods: Twenty-five patients with PD performed a series of tasks throughout a levodopa challenge while wearing sensors. TRIS was used to determine motor changes in pronation-supination tests following a single levodopa dose, and was compared to clinical ratings including the Treatment Response Scale (TRS) and six sub-items of the UPDRS part III. Results: As expected, correlations between TRIS and clinical ratings were lower in the new population than in the initial study. TRIS was still significantly correlated to TRS ( r s  = 0.23, P  < 0.001) with a root mean square error (RMSE) of 1.33. For the patients (n = 17) with a good levodopa response and clear motor fluctuations, a stronger correlation was found ( r s  = 0.38, RMSE = 1.29, P  < 0.001). The mean TRIS increased significantly when patients went from the practically defined off to their best on state ( P  = 0.024). Individual dose-response models could be fitted for more participants when TRIS was used for modelling than when TRS ratings were used. Conclusion: The objective sensor index shows promise for constructing individual dose-response models, but further evaluations and retraining of the TRIS algorithm are desirable to improve its performance and to ensure its clinical effectiveness. Highlights: A previously developed objective sensor index for treatment effects was evaluated in a new PD population. The objective sensor index performed better in patients with acute levodopa response and clear motor fluctuations. The objective sensor index shows promise for constructing individual dose-response models.